PROFITABILITY OF ADOPTING PESTE DES PETITS RUMINANTS VACCINE IN DHADING, NEPAL - Mahesh Dutta Chaulagain; Suryamani Dhungana; Chandan KC (Science Heritage Journal)
A study was conducted to understand the Profitability of Peste des Petits (PPR) vaccine adoption in Dhading district, Nepal to determine whether PPR vaccinated goats generate higher profits for female goat keepers and to identifying the associated barriers of PPR vaccine adoption. Altogether 120 households were selected using random sampling technique. Primary data were collected using semi-structured and pre- tested household questionnaire, FGDs and KIIs while secondary data were collected from different published records. Both descriptive and inferential statistics were used to analyze the data. Data were encoded and analyzed excel, SPSS and R-Stat. In subsistence goat farming, the average production cost per goat was NRs.4226 annually, with BCR of 2.05. The vaccinated goats farming have BCR of 4.69 while unvaccinated goats farming has 1.61 BCR, which suggest that the goat farm adopted with PPR vaccination is profitable. Among 13 barriers of vaccine adoption explored the communication in between goat keepers and CAHW and Education status of farmers are more likely to enhance the adoption of PPR vaccine. PPR vaccine adoption is driven by an integrated approach that binds the responsibility of goat farmers, community, local government and national level institutes including government and non-government organizations which help to increase women’s economic and social empowerment and contribute to more sustainable agribusiness through equitable subsistence goat farming systems. Moreover, it is important to establish a reliable information system within the cooperative to ensure that farmers receive timely and accurate information about vaccination campaigns and elongate the duration of vaccination campaign.